Highly efficient classes of algorithms and high-performance systems implementing the synchronous interaction networks with data-processing systolic matrices - Hrytsyk, V. V.; Hrytsyk, V. V.; Zozulya, A. M. (Reports of the National Academy of Sciences of Ukraine, 2015)
High-performance computing systems implementing the synchronous interaction networks with data-processing systolic matrix are defined. Some possibilities for the data processing in real time with VLSIC's oriented to solving the computer vision problems in various fields are proposed.